The influence of Piracetam and Phenotropil on brain dopamine and serotonin metabolism in CD-1 mice sub-populations, diverging in attention sustainability - N. A. Sukhorukova; V. S. Kudrin; V. B. Narkevich; G. I. Kovalev (LLC "Publisher OKI", 2022)
The effect of subchronic administration of the nootropics Phenotropil (100 mg/kg/day) on the behavior of CD-1 outbreed mice in the "closed enriched cross maze" test (CECM) was studied. Predominantly, the mouse population was divided into subpopulations according to their values of individual attention index for novel objects in the maze compartments - highly attentive (ED-high) and low attentive (ED-low). It was found that Phenotropil increased the attention index in ED-low, but disimproved it in the ED-high subpopulation, and also changed parameteres of anxiety and locomotor activity; this distinguished it from the more selective effect of Piracetam (200 mg/kg/day). The higher selectivity of Piracetam was also shown in relation to dopamine metabolism processes in the prefrontal cortex: the drug normalized the metabolic turnover of intracellular (DOPAC/DA) as well as extracellular (HVA/DA) dopamine, while Phenotropil influenced on the former only. Thus, positive effect of Piracetam on the attention level in ED-low mice corresponds to the normalization of both indicators of dopamine metabolism in the prefrontal cortex, while Phenotropil showed non-selectivity onto both behavioral and neurochemical parameters. Piracetam and Phenotropil failed to affect the cortical and striatal serotonin metabolism in both subpopulations.